Characteristics of the Spatial Location of Sports Facilities in the Northern Great Plain Region of Hungary - Gábor Kozma; Károly Teperics; Klára Czimre; Zsolt Radics (MDPI AG, 2022)
Sports facilities play a very important role in educating people about the benefits of a healthy lifestyle, and the examination of their spatial distribution is one of the important research areas of sport geography, a field of study becoming increasingly important in recent times. In this spirit, the aim of this paper is to present the spatial distribution of sports facilities in a specific Hungarian sample area, the Észak-Alföld (Northern Great Plain) region, to point out the differences between settlements, as well as the reasons behind these differences. Data received from the local authorities and state administration bodies were used for the preparation of the study, which included the different sports facilities at the settlement level in addition to information found on the Internet. The following conclusions were drawn based on the research. First of all, it was found that the settlement size significantly influences the spatial distribution of sports facilities, inter alia, larger settlements with larger populations boast increased demand and higher purchasing power and also have more enhanced and more diverse sports infrastructure. Secondly, in the case of competitive sports, the size of settlements is less relevant; there are only insignificant differences between the settlements of different sizes. This can be explained by the fact that almost all settlements have their own football pitch. Thirdly, the administrative role of the settlements was also found to be significant since settlements being on higher levels of the hierarchy (district centres, county seats) always have better facilities.